1994
DOI: 10.1084/jem.180.3.841
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of class I major histocompatibility complex gene expression in primary sensory neurons, satellite cells, and Schwann cells of mice in response to acute but not latent herpes simplex virus infection in vivo.

Abstract: Major histocompatibility complex (MHC) deficiency is typical of almost all resident cells in normal neural tissue. However, CD8+ T cells, which recognize antigenic peptides in the context of class I MHC molecules, are known to mediate clearance of herpes simplex virus (HSV) from spinal ganglia of experimentally infected mice, leading to the hypothesis that class I expression in the peripheral nervous system must be upregulated in response to HSV infection. In addressing this hypothesis it is shown, in BALB/c (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 37 publications
(45 reference statements)
5
46
1
Order By: Relevance
“…An inability to detect the class I protein in neurons might result from the lack of a suitable, high-affinity antibody for nonclassical MHC class I proteins, and not due to the absence of expression of these molecules in vivo. Our data are consistent with the findings of Pereira et al that primary sensory neurons upregulate MHC class I mRNA, but not class I proteins, in response to acute herpes simplex virus infection (36). However, in a subsequent study, low-density classical class I proteins were demonstrated by flow cytometry on the cell surface of dissociated primary sensory neurons recovered from mice infected with herpes simplex virus (35).…”
Section: Discussionsupporting
confidence: 82%
“…An inability to detect the class I protein in neurons might result from the lack of a suitable, high-affinity antibody for nonclassical MHC class I proteins, and not due to the absence of expression of these molecules in vivo. Our data are consistent with the findings of Pereira et al that primary sensory neurons upregulate MHC class I mRNA, but not class I proteins, in response to acute herpes simplex virus infection (36). However, in a subsequent study, low-density classical class I proteins were demonstrated by flow cytometry on the cell surface of dissociated primary sensory neurons recovered from mice infected with herpes simplex virus (35).…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, an immediate early gene product of HSV has the capacity to shut off cell surface expression of class I MHC molecules in infected cells (17), perhaps hindering their immunologic destruction and allowing their recognition by IFN-producing NK cells. In addition, HSV can up-regulate class I MHC expression in neighboring uninfected neurons (18), potentially enabling rapid presentation of virion structural proteins at the cell surface for perusal by cells bearing TCRs (T or NK/T cells) before the onset of viral gene expression. In summary, a genetic locus, Rhs1 r , was responsible for minimizing the magnitude of productive HSV infection in the sensory nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, gB gene expression would be very low during the early stages of HSV-1 reactivation from latency in neurons. Moreover, neurons typically express very low levels of MHC class I, but appear to up-regulate expression during the HSV-1 lytic cycle (25,26). Thus, it is likely that neurons express a low density of the gB 498 -505 epitope early in the reactivation process.…”
Section: Discussionmentioning
confidence: 99%